Some Fixed Point Theorems in Dislocated Quasi b-metric Spaces - Ch. Srinivasa Rao; K. Satya Murthy; S. S. A. Sastri; K. Sujatha (International Journal of Mathematics And its Applications, 2019)
In this paper we have given a fixed point theorem in dislocated quasi b-metric spaces which is generalization of dislocated quasi metric, partial b-metric spaces and the Banach contraction principle.